HPV virus as the main cause of cervical cancer, vaccination - literature review - Michał Paluch; Michał Tomkiewicz; Paweł Olko; Jakub Radulski; Piotr Sałata; Magda Żuchnik; Hugo Szczuraszek; Paulina Szczuraszek; Agnieszka Rybkowska; Julia Tomkiewicz (Kazimierz Wielki University, 2023)
HPV infection is one of the most common viral infection of the female and male reproductive tract worldwide. Most of the human papillomavirus infections cause no symptoms and go away on their own. Some infections develop into persistent infection, which can lead to the development of cancer of the cervix, anogenital, oral cavity and pharynx.In this paper, we focused on cervical cancer, which is the second most common cancer in the world among women. More than 300,000 women died from this cancer in 2020. The invention and introduction of prophylactic HPV vaccines has played a significant role in reducing the number of viral infections, thus reducing the incidence of benign and malignant diseases caused by them and the mortality resulting from them. There are three vaccines on the pharmaceutical marketfor prevention of specific HPV infection. They are: a bivalent vaccine Cervarix, a tetravalent vaccine Gardasil and a nonavalent vaccine Gardasil 9. These vaccines are safe because they do not contain an attenuated virus particle, but their production is based on a virus-like particle of the main capsid protein L1-VLP. Gardasil 9 targets nine HPV types andcomparing to the other two vaccines it is the most effective at preventing the development of preinvasive cervical cancer. WHO recommends administering them to girls aged 9 to 14 in a two-dose schedule or from 15 years of age in a three-dose schedule. The side effects of the above-mentioned vaccines were mostly associated with a cutaneous reactions around the site of injection (pain, redness, swelling), and some people also experienced systemic symptoms such as a headache, a fever, vomiting, a dizziness, muscle pain and a diarrhea. The following article is an analysis of the current knowledge on the effectiveness and safety of prophylactic HPV vaccines based on publications available in the Pubmed and Google Scholar databases.